Penyelesaian Sengketa Informasi Publik Perspektif Di Peradilan Tata Usaha Negara Di Indonesia: Komisi Informasi, Pengadilan Tata Usaha Negara, Penyelesaian Sengketa Informasi Sinkronisasi - Nilam Kurnia; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
Regarding the existence of a state administrative court, we must look at the country next to us such as France, a country which historically was the pioneer of the birth of this kind of institution for the first time. The role of the French state is still felt today. the state acts as a leader in the "Association Internationale des Houtes Administrative Jurisdiction".